Kajian daya cerna pati cookies kecambah sorgum (Sorghum bicolor [L.] Moench) dengan tersubstitusi tepung kacang tunggak (Vigna unguiculata L.) - Endah Wulandari; Zaida Zaida; Devi Ariska (Composite : Jurnal Ilmu Pertanian, 2022)
The high use of wheat flour today makes Indonesia dependent on wheat imports. One of the commodities that can replace wheat is sorghum (Sorghum bicolor [L.] Moench), this is confirmed by various studies. The purpose of this study was to determine the balance of sorghum flour and cowpea flour as raw materials for making cookies which have high starch digestibility characteristics. This study used a Randomized Block Design (RAK) method which consisted of six treatments and three replications. The treatments were the proportions of sorghum flour and cowpea flour of 90:10, 80:20, 70:30 and the proportions of sorghum sprouts flour and cowpea flour were 90:10, 80:20, 70:30. The results showed that cookies with sorghum sprouts flour and cowpea flour 90:10 were the best treatment with 23.35% starch digestibility. Keywords: Cookies, Sorghum, Starch Digestibility.